Substitution effect on chalcone based materials for corrosion and photocrosslinking applications. Issue 1 (1st December 2014) - Ramkumar, V.; Anandhi, S.; Kannan, P.; Gopalakrishnan, R.
Abstract : Hydroxy (–OH) and benzyloxy (–OCH2 Ph) substituted chalcone based crystalline materials were synthesized and characterized; these materials exhibited high corrosion inhibitor efficiency and enhanced photo-crosslinking applications. Abstract : Three different substituted novel chalcone based materials namely ( E )-3-(4-(benzyloxy)phenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one (chalconeI ), ( E )-1-(4-(benzyloxy)phenyl)-3-(4-hydroxyphenyl)prop-2-en-1-one (chalconeII ) and ( E )-1, 3-bis(4-(benzyloxy)phenyl)prop-2-en-1-one (chalconeIII ) were designed and synthesized by a standard Claisen–Schmidt condensation reaction. The different surface morphologies of these materials were obtained from SEM (Scanning Electron Microscopy) analysis. Single crystal XRD studies of chalconeIII indicate a monoclinic system with a space group of P 21 / c . Thermal studies such as TGA, DSC and HOPM revealed good thermal stability, crystallinity and phase changing properties of materialIII . The HOMO, LUMO and bandgap energies of these three materials were calculated by theoretical (DFT) calculations. The electrochemical analysis involves Tafel plots and cyclic voltammetry studies to demonstrate high corrosion inhibition percentage and oxidation–reduction behaviour of materialsI, II andIII . Dissimilar photocrosslinking time of all three materials was obtained from micro photo-reactor and UV-visible spectrophotometry. The comparative and structural linearity statement reveals the outline view property of the similar chalcone families.